Indonesian-English Code-Switching of Sacha Stevenson as a Canadian Bilingual Speaker on YouTube - Astrid Tiara Rini; Rio Rini Diah Moehkardi (Lexicon, 2020)
Code-switching or language alternation is one of the linguistic strategies that is widely used in bilingual community, including Indonesia. This study attempts to find out the types and reasons of code-switching on YouTube as employed by a Canadian bilingual speaker, Sacha Stevenson. The data used for this study were transcripts of five videos about Indonesian culture taken from Sacha’s YouTube channel. Based on the analysis, there are a total of 313 occurrences of code-switching from Indonesian to English. Poplack’s theory (1980) was applied for the classification of code-switching. The findings showed that the most frequent type is inter-sentential code-switching (42%), followed by intra-sentential code-switching (34%), and the least is tag-switching (24%). This study also explored the reasons for code-switching by applying the theory proposed by Grosjean (1984). It was found that all code-switching occurrences fit into the 11 categorizations of code-switching reasons. This shows a variety of different factors that influence the use of code-switching. The most frequent reason which triggered code-switching is to fill a linguistic need for lexical item, set phrase, discourse marker, or sentence filler (31%). In addition to the 11 reasons proposed by Grojean (1984), another reason for code-switching was found, i.e., to gain popularity.